2014
DOI: 10.1038/ki.2014.225
|View full text |Cite
|
Sign up to set email alerts
|

Results of the HepZero study comparing heparin-grafted membrane and standard care show that heparin-grafted dialyzer is safe and easy to use for heparin-free dialysis

Abstract: Results of the HepZero study comparing heparin-grafted membrane and standard care show that heparin-grafted dialyzer is safe and easy to use for heparin-free dialysis Gambro-Hospal, Meyzieu, FranceHeparin is used to prevent clotting during hemodialysis, but heparin-free hemodialysis is sometimes needed to decrease the risk of bleeding. The HepZero study is a randomized, multicenter international controlled open-label trial comparing no-heparin hemodialysis strategies designed to assess non-inferiority of a he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 23 publications
3
64
1
1
Order By: Relevance
“…The use of heparin pregrafted membranes increases the rate of successful heparin-free intermittent hemodialysis sessions in high bleeding risk patients [60] and allows for a reduction of systemic heparin dosing, without compromising the dialysis session [61]. However, none of the published studies assessing the oXiris ® membrane has specifically evaluated its antithrombogenic properties in the setting of acute septic patients and CRRT.…”
Section: Antithrombogenic Treatmentmentioning
confidence: 99%
“…The use of heparin pregrafted membranes increases the rate of successful heparin-free intermittent hemodialysis sessions in high bleeding risk patients [60] and allows for a reduction of systemic heparin dosing, without compromising the dialysis session [61]. However, none of the published studies assessing the oXiris ® membrane has specifically evaluated its antithrombogenic properties in the setting of acute septic patients and CRRT.…”
Section: Antithrombogenic Treatmentmentioning
confidence: 99%
“…By rinsing in unfractionated heparin saline, the membrane is primed with a heparin layer, which reduces membrane thrombogenicity [7, 8]. Previous studies have reported successful heparin-free extracorporeal circulation with the AN69ST filter for a maximum 6 h. However in the HepZero study [10, 12] reported by Laville M et al, the risk of premature clotting during 4-h hemodialysis reached more than 30% by use of a heparin-coated dialyzer, although it resulted in a higher success rate when compared with standard heparin-free hemodialysis (68.5% vs. 50.4%, respectively). Similarly in the present prospective, randomized self-controlled study, PI-RRT was completed for a duration of 543.1 ± 119.0 min in only 51.7% of patients using an AN69ST hemofilter.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with contraindications to systemic anticoagulation, options include heparin-free HD (regular saline flushing of the circuit), regional citrate anticoagulation 2 or use of dialysers with heparin-coated membranes. 3 …”
Section: The Dialysis System: Technical Considerationsmentioning
confidence: 97%